Upper Respiratory Tract Infections in Athletes - Page, Clifton L. (Clin Sports Med, 2007)
Upper respiratory tract infections (URTIs) represent the most common acute illnesses in the general population and account for the leading acute diagnoses in the outpatient setting. Given the athlete's expectation to return to activity as soon as possible, the sports medicine physician should be able to accurately diagnose and aggressively treat these illnesses. This article discusses the common pathogens, diagnosis, treatment options, and return-to-play decisions for URTIs, with a focus on the common cold, sinusitis, pharyngitis, and infectious mononucleosis in the athlete.